STUDY OF CATION ORDER-DISORDER IN MGAL2O4 SPINEL BY IN SITU NEUTRON DIFFRACTION UP TO 1600 K AND 3.2 GPA - Méducin F.; Redfern S.A.T.; Stone H.J.; Tucker M.G.; Dove M.T.; Le Godec Y.; Marshall W.G. (My University, 2004)
The temperature-dependence of the cation distribution in synthetic spinel (MgAl2O4) was investigated using in situ time-of-flight neutron powder diffraction at ISIS, the pulsed-neutron source at the Rutherford Appleton Laboratory. Neutron diffraction patterns of stoichiometric MgAl2O4 were collected on heating from room temperature to ∼1600 K at pressures of ∼2.6 GPa. The cation distribution was determined directly from site occupancies obtained by Rietveld refinement. The equilibrium non-convergent ordering was analyzed using the OʼNeill-Navrotsky (1983) thermodynamic model, which fits the observed behavior well over the temperature range of the measurements. Fitting the data between 790 and 1600 K yields α = 31(6) kJ/mol and β = -20(13) kJ/mol in the expression for the free energy of ordering. The high-pressure temperature-dependent behavior, as compared to equivalent ambient-pressure behavior, demonstrates that disordering occurs to a much greater extent in MgAl2O4 at high pressure and that pressure favors disordering toward the inverse structure.
Keywords: spinel